Tc-99m-Tetrofosmin Scintigraphy: An Alternative Scintigraphic Method for Following up Differentiated Thyroid Carcinoma - Gallowitsch, H. J.; Kresnik, E.; Mikosch, P.; Pipam, W.; Gomez, Iris; Lind, P. (Nuklearmedizin - NuclearMedicine, 1996)
Aim: The usefulness of the myocardial perfusion agent, Tc-99m-tetrofosmin (Myoview®) in the follow-up of differentiated thyroid carcinoma was evaluated in a clinical study of 15 patients, primary treated with thyroidectomy and high-dose I-131-therapy (2960-3700 MBq), 12 with suspected recurrence and metastases and three patients without any suspicion and compared with other non-specific tracers like TI-201 and Tc-99m-sestamibi. Method: Twelve patients with elevated thyroglobulin (Tg) levels of more than 10 ng/ml (group A), four of these had negative I-131 scans, and three patients with Tg levels less than 10 ng/ml (group B) were examined under TSH suppressive L-Thyroxine treatment. Whole body scans were taken with TI-201 (74 MBq; 20 min post injection), Tc-99m-sestamibi (370 MBq; 20-60 min post injection) and Tc-99m-tetrofosmin (370 MBq; 20-60 min post injection). Tumor/background ratios and optional time/activity analyses (up to 150 min post injection) were evaluated using the region of interest approach. Results: Compared with TI-201 (T/BG: 1.59, ± 0.396), Tc-99m-tetrofosmin showed slightly but not significant better T/BG ratios and detection rates (T/BG: 1.76, ± 0.345).Tc-99m-sestamibi (1.51, ± 0.31 p = 0.05) showea significantly lower values than Tc-99m-tetrofosmin. Conclusion: In the light of these results, scintigraphy with Tc-99m-tetrofosmin seems to be a possibly sensitive imaging modality in the follow-up of DTC with possible advantages concerning T/Bg ratio, background clearance, detection rate and dosimetry compared with TI-201 and Tc-99m-sestamibi, especially in patients with elevated Tg level and no iodine uptake , but further investigations are needed to confirm our preliminary results.
Keywords: Differentiated thyroid carcinoma; TI-201; Tc-99m-sestamibi; Tc-99m-tetrofosmin